Governance for the forest management in the micro-watersheds of La Esperanza and Lancetilla rivers in the Atlántida Model Forest, Honduras - Ponce Salgado, Jeremy A. (2011)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2011